2014
DOI: 10.4049/jimmunol.1303145
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cross-Protection by Genetically Modified Live-Attenuated Leishmania donovani Parasites against Leishmania mexicana

Abstract: Previously, we showed that genetically modified live-attenuated Leishmania donovani parasite cell lines (LdCen−/− and Ldp27−/−) induce a strong cellular immunity and provide protection against visceral leishmaniasis in mice. In this study, we explored the mechanism of cross-protection against cutaneous lesion-causing Leishmania mexicana. Upon challenge with wild-type L. mexicana, mice immunized either for short or long periods showed significant protection. Immunohistochemical analysis of ears from immunized/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 73 publications
2
43
0
Order By: Relevance
“…Importantly LmCen -/- parasites elicited protection against sand fly challenge that was deemed necessary but was neither performed or was not demonstrated in previous vaccination studies 20,38,41,42 . These observations using a cutaneous model of infection are consistent with our previous findings that immunization with LdCen-/- parasites were protective against visceral leishmaniasis in different animal models 2628,30,46 .…”
Section: Discussionsupporting
confidence: 92%
“…Importantly LmCen -/- parasites elicited protection against sand fly challenge that was deemed necessary but was neither performed or was not demonstrated in previous vaccination studies 20,38,41,42 . These observations using a cutaneous model of infection are consistent with our previous findings that immunization with LdCen-/- parasites were protective against visceral leishmaniasis in different animal models 2628,30,46 .…”
Section: Discussionsupporting
confidence: 92%
“…Recently F1 epitopes derived of nucleoside hydrolase, a component of Leishmune , from L. donovani protected BALB/c mice from the challenge with L. amazonensis , however, immunized mice treated with anti‐CD8 monoclonal antibody abrogated the protective efficacy of this vaccine candidate. The study conducted by Dey and collaborators showed that BALB/c mice immunized with genetically modified live‐attenuated L. donovani and challenge with L. (L.) mexicana presented, mainly, high frequencies of CD8 + IFN‐γ + . Taken together, these studies suggest an essential function of CD8 T lymphocytes for resistance against leishmaniasis during vaccination, as previously related .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Briefly, bone marrow cells were isolated from femurs and tibias of mice, treated with ACK lysis buffer and plated @ 5 million cells/ plate in sterile 100 £ 15 mm vented petri dishes along with complete RPMI medium supplemented with 10% fetal bovine serum (Atlanta Biologicals), 1% penicillin (20 Units/mL)/streptomycin (20 mg/mL) (Life Technologies) and 20ng/mL GMCSF (Peprotech) for 6 d At Day 6, cells from DC culture were collected by gently harvesting the floating fraction of cells to obtain >75% purity of CD11c C DCs in the floating fraction. The remaining cells in the floating fraction did not display lineage specific markers for T cells, B cells, NK cells and macrophages upon flow cytometric analysis.…”
Section: Cultivation and Stimulation Of Bone Marrow Derived Dendriticmentioning
confidence: 99%